An analytical-numerical approach for parameter determination of a five-parameter single-diode model of photovoltaic cells and modules. Issue 4 (20th April 2016) - Hejri, Mohammad; Mokhtari, Hossein; Azizian, Mohammad Reza; Söder, Lennart
Abstract : Parameter extraction of the five-parameter single-diode model of solar cells and modules from experimental data is a challenging problem. These parameters are evaluated from a set of nonlinear equations that cannot be solved analytically. On the other hand, a numerical solution of such equations needs a suitable initial guess to converge to a solution. This paper presents a new set of approximate analytical solutions for the parameters of a five-parameter single-diode model of photovoltaic (PV) cells and modules. The proposed solutions provide a good initial point which guarantees numerical analysis convergence. The proposed technique needs only a few data from the PV current-voltage characteristics, i.e. open circuit voltage V oc, short circuit current I sc and maximum power point current and voltage I m ; V m making it a fast and low cost parameter determination technique. The accuracy of the presented theoretical I–V curves is verified by experimental data.